Vpliv intervalov odmora na izvedbo skoka z nasprotnim gibanjem po seriji skokov z nasprotnim gibanjem nizke intenzivnosti z obremenitvijo - Tan, I. J. L.; Cua, M. H.; Pagaduan, J. C.; Pojskic, H.; Uzicanin, E.; Babajic, F. (Kinesiologia Slovenica, 2013)
The purpose of the study was to determine the influence of varying rest intervals on countermovement jump (CMJ) performances following low-intensity loaded countermovement jumps (LCMJs). Twenty-nine collegiate football players (age: 19.4 ± 1.1 years; height: 179.0 ± 5.1 cm; weight: 73.1 ± 8.0) from Tuzla University volunteered to participate in the study. They performed ten LCMJs using 15% of their 1 repetition maximum (1RM) squat. The subjects then executed a CMJ every 2 minutes until a total of 6 jumps had been completed. One-way repeated measures ANOVA showed significant differences in countermovement jump heights at various rest intervals, F(2.23, 62.3) = 40.5, p